Multidrug resistance protein gene expression in Trichoplusia ni caterpillars. Issue 1 (21st November 2012) - Simmons, Jason; D'Souza, Olivia; Rheault, Mark; Donly, Cam
Abstract Many insect species exhibit pesticide‐resistant phenotypes. One of the mechanisms capable of contributing to resistance is the overexpression of multidrug resistance (MDR) transporter proteins. Here we describe the cloning of three genes encoding MDR proteins from Trichoplusia ni: trnMDR1, trnMDR2 and trnMDR3. Real‐time quantitative PCR (qPCR) detected trnMDR mRNA in the whole nervous system, midgut and Malpighian tubules of final instar T. ni caterpillars. To test whether these genes are upregulated in response to chemical challenge in this insect, qPCR was used to compare trnMDR mRNA levels in unchallenged insects with those of insects fed the synthetic pyrethroid, deltamethrin. Only limited increases were detected in a single gene, trnMDR2, which is the most weakly expressed of the three MDR genes, suggesting that increased multidrug resistance of this type is not a significant part of the response to deltamethrin exposure.